2006
DOI: 10.1029/2005jb003647
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric structure beneath trans‐Carpathian transect from Precambrian platform to Pannonian basin: CELEBRATION 2000 seismic profile CEL05

Abstract: [1] In 2000, a consortium of European and North American institutions completed a huge active source seismic experiment focused on central Europe, the Central European Lithospheric Experiment Based on Refraction or CELEBRATION 2000. This experiment primarily consisted of a network of seismic refraction profiles that extended from the East European craton, along and across the Trans-European suture zone region in Poland to the Bohemian massif, and through the Carpathians and eastern Alps to the Pannonian basin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 49 publications
11
116
0
2
Order By: Relevance
“…2). These data are in accord with the results from gravimetry and refraction seismic measurements (Vozár et al, 1999;Grad et al, 2006). It seems that the crystalline massif of the Tribeč mountain range is composed of a couple of physically different lithological environments with notable differences between the individual resistance values.…”
Section: Geophysical Input Datasupporting
confidence: 81%
“…2). These data are in accord with the results from gravimetry and refraction seismic measurements (Vozár et al, 1999;Grad et al, 2006). It seems that the crystalline massif of the Tribeč mountain range is composed of a couple of physically different lithological environments with notable differences between the individual resistance values.…”
Section: Geophysical Input Datasupporting
confidence: 81%
“…In the Carpathian-Pannonian region it has been observed that this P-wave velocity interval is valid for the whole crust (e.g. Grad et al, 2006;Hrubcová et al, 2005;Růžek et al, 2006;Środa et al, 2006 ).…”
Section: Real Data Transformationmentioning
confidence: 99%
“…The seismic results of CELEBRATION 2000 profiles (e.i., Grad et al, 2006;Środa et al, 2006;Janik et al, 2011 ) brought very good information on the P-wave velocity distribution in the crust and in the upper part of the mantle in the Carpathian-Pannonian region. It allowed us to transform the crustal P-wave velocities to densities.…”
Section: Introductionmentioning
confidence: 99%
“…This is a rare situation for known interpretations of the potential source bodies with high electric conductivity of ionic type (e.g. Ernst et al, 2002;Grad et al, 2006 andJankowski et al, 2008).…”
Section: Analysis Of Data and Interpretationmentioning
confidence: 99%